On opportunity for emergency cesarean hysterectomy and pregnancy outcomes of patients with placenta accreta - Kong, Xiang (Medicine (Baltimore), 2017)
Effective diagnosis and clinical management of placenta accreta (PA) in China are not clear. The purpose of the study was to analyze the risk factors and diagnosis of PA, maternal and neonatal outcomes in patients with PA. It was a retrospective study of cases with PA, confirmed by histologically and/or clinically suspected during 3 years in 2 tertiary referral hospitals. The incidence rate of patients with PA, who had history of artificial abortion, cesarean section (CS), and placenta previa (PP) was 94%, 70%, and 72%, respectively. In 29 patients of scheduled CS group, 12 cases were performed with cesarean hysterectomy. Mean estimated blood loss (EBL) was 1.5 L, and 17 babies were admitted to neonatal intensive care unit (NICU). In the 18 cases of emergency CS group, 6 cases were performed cesarean hysterectomy. Mean EBL was 2.4 L, and 16 babies were admitted to NICU. The difference of mean EBL, cases of fetal admitted to intensive care unit in 2 groups was significant difference (P < .05). Women with history of uterine curettage, CS or PP are more likely to have PA. PA should be diagnosed early and accurately via ultrasound and magnetic resonance imaging. Maternal and neonatal outcomes in the scheduled CS are better than in emergency CS. Emergency peripartum hysterectomy is a feasible method under the circumstances of heave, fast bleeding, and the failure of conservative surgery.